Changes in the structure of the tourist function in Kujawy spas (based on the volume and structure of tourist traffic) - Matczak, Andrzej (Turyzm/Tourism, 2019)
The purpose of the paper is to identify changes in the structure of the tourism function in Kujawy spas which have led to their transformation into tourism and health resorts. The study was based on tourist traffic statistics referring to the period 2000-2017 and included defining the relationship between curative and other forms of tourist traffic. The author has used a wide range of statistical data, as well as information provided by surveys to determine and analyze the statistical indicators of tourist traffic pace, intensity and structure. The analysis reveals a significant transformation of the spas in Kujawy. This is confirmed by the indicators of curative and non-curative tourist traffic and by the reasons for visiting health resorts. The pace of changes in the tourism function in individual spas is varied. It is fastest in Ciechocinek, accelerating in Wieniec-Zdrój and slowest in Inowrocław. The changes occurring in the spas are causing their gradual transformation into tourism and health resorts.